Understanding profiles of student binge drinking and eating: The importance of motives. (September 2019) - Trojanowski, Paige J.; Adams, Leah M.; Fischer, Sarah
Abstract: Binge drinking and binge eating occur frequently in undergraduates; however, the mechanism driving their co-occurrence is not well-understood. Several theories support the role of motives in driving drinking and eating behavior, especially motivations related to affect regulation (i.e., enhancement/pleasure and coping). This study used a person-centered approach to identify classes of students based on eating and drinking motives and past-month binge behavior and examined class differences in psychopathology, emotion regulation, and impulsivity. Undergraduates ( N  = 776) completed a drinking timeline follow-back and surveys assessing motives, binge eating, psychopathology, emotion regulation, impulsivity, and quality of life. Mixture modeling was used to group students based on presence/absence of past-month binge eating, binge drinking, and motives for eating and drinking. The analysis resulted in 4 classes: Binge Drinking (with relatively high social and enhancement drinking motives), Binge Eating (with overall high eating motives), Both Bingeing (with high drinking motives, especially coping, and high eating motives), and Low Bingeing (with low motives for both behaviors). ANOVA and post-hoc analyses suggested that the Binge Eating and Both Bingeing groups were most impaired, while the Binge Drinking class rarely differed from the Low Bingeing group across measures of psychological distress. Notably, classes with high eating/drinking motives displayed significant impairment despite not all class members endorsing binge behavior. Findings suggest that binge drinking in addition to binge eating may not imply more psychological impairment and support the importance of assessing motives for eating/drinking among undergraduates and potentially trying to challenge these motives through early intervention. Highlights: Person-centered approaches help accurately capture student binge eating and drinking profiles. Eating/drinking motives may improve classification beyond clustering by binge status only. Comorbid binge class generally did not show more psychological distress than Binge Eating class. Binge Drinking class displayed a psychological profile similar to Low Bingeing class. High eating and drinking motives were associated with distress for some students who did not binge.